2021
DOI: 10.3389/fmed.2021.714958
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as Novel Diagnostic Biomarkers and Therapeutic Targets in Kidney Disease

Abstract: Circular RNAs (circRNAs) are a novel type of non-coding RNAs that have aroused growing attention in this decade. They are widely expressed in eukaryotes and generally have high stability owing to their special closed-loop structure. Many circRNAs are abundant, evolutionarily conserved, and exhibit cell-type-specific and tissue-specific expression patterns. Mounting evidence suggests that circRNAs have regulatory potency for gene expression by acting as microRNA sponges, interacting with proteins, regulating tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Finally, we have identified several circRNAs that may associate with nephrotic syndrome, their downregulated expression in patients will lead to the upregulation of their targeting miRNAs, inducing targeting mRNAs to be upregulated and then generate the nephrotic syndrome. The mechanisms by which these circRNAs interact with miRNAs and mRNAs are unclear, but these circRNAs may be potential targets for the treatment of kidney disease, in line with the findings of Yu et al that circRNAs are novel diagnostic biomarkers and therapeutic targets for kidney disease [ 38 ], but whether these circRNAs can be biomarkers for nephrotic syndromes requires further testing.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, we have identified several circRNAs that may associate with nephrotic syndrome, their downregulated expression in patients will lead to the upregulation of their targeting miRNAs, inducing targeting mRNAs to be upregulated and then generate the nephrotic syndrome. The mechanisms by which these circRNAs interact with miRNAs and mRNAs are unclear, but these circRNAs may be potential targets for the treatment of kidney disease, in line with the findings of Yu et al that circRNAs are novel diagnostic biomarkers and therapeutic targets for kidney disease [ 38 ], but whether these circRNAs can be biomarkers for nephrotic syndromes requires further testing.…”
Section: Discussionmentioning
confidence: 73%
“…CircRNA is fine-tuned and controlled in many physiological and pathological conditions, and could trigger a significant breakthrough in CKD prevention. Mounting evidence has shown that circRNA expression is altered in kidney disorders ( van Zonneveld et al, 2021 ; Yu et al, 2021 ). However, the identification and function of circRNAs are largely unknown in the context of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (circRNA) are endogenous regulatory single-stranded, covalently closed RNA molecules that have recently attracted the attention of researchers studying their involvement in disease development as markers and potential molecular targets [ 49 , 50 , 51 ]. Recently, analogues of these natural RNAs have been proposed as synthetic inducers of RNAi—circular small interfering RNAs (csiRNAs).…”
Section: Circular Small Interfering Rnas (Csirna)mentioning
confidence: 99%